PENGARUH CASHBACK, FLASH SALE DAN SHOPEE PAYLATER TERHADAP IMPULSE BUYING PENGGUNA E-COMMERCE SHOPEE PADA MAHASISWA UNIVERSITAS NUSANTARA PGRI KEDIRI - Hevinias, Astin Sarah; Dyah Puspasari, Ismayantika; Ayu Paramitha, Dyah (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
This study aims to analyze the Influence of Cashback, Flash Sales, and Shopee PayLater on Impulse Buying in Shopee e-commerce, both partially and simultaneously. The population in this study includes all students of Universitas Nusantara PGRI Kediri. The sampling technique in this study used purposive sampling, where the sample was only taken from students who were Shopee users and utilized the Shopee Paylater payment feature. The number of samples used in this study was 72 respondents. The analysis methods used in this study include the Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test and Hypothesis Test with the help of IBM SPSS version 23. The results of this study indicate that (1) partially cashback, shopee paylater have an effect on impulse buying, while flash sale has no effect on impulse buying (2) simultaneously cashback, flash sale and shopee paylater have an effect on impulse buying